2009
DOI: 10.1103/physrevlett.103.166101
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Dome-Shaped Carbon Nanoislands on Ir(111): The Intermediate between Carbidic Clusters and Quasi-Free-Standing Graphene

Abstract: By combining high-resolution photoelectron spectroscopy and ab initio calculations, we show that carbon nanoislands formed during the growth of a long-range ordered graphene layer on Ir(111) assume a peculiar domelike shape. The understanding of the unusual growth mechanism of these C clusters, which represent an intermediate phase between the strongly coupled carbidic carbon and a quasi-free-standing graphene layer, can provide information for a rational design of graphenelike systems at the nanoscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
150
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 20 publications
26
150
0
2
Order By: Relevance
“…Cluster precursors to graphene growth using TPG have also been reported on Ir(111) [139] and Ru(0001) [275] surfaces. For coronene and ethene deposition onto a Ru(0001) surface two cluster types were found at 900 K, see Fig.…”
Section: Cluster Formationmentioning
confidence: 96%
See 1 more Smart Citation
“…Cluster precursors to graphene growth using TPG have also been reported on Ir(111) [139] and Ru(0001) [275] surfaces. For coronene and ethene deposition onto a Ru(0001) surface two cluster types were found at 900 K, see Fig.…”
Section: Cluster Formationmentioning
confidence: 96%
“…These include crystalline substrates such as Cu(111) [253], Ni(111) [254,255], Co(0001) [256,257], Fe(110) [258], Au(111) [259], Pd(111) [62], Pt(111) [58], Re(1010) [260], Ru(0001) [106], Rh(111) [261], Ir(111) [61,139,54,92], but also polycrystalline surfaces [262,263,252] and thin films evaporated onto a different bulk material [264,265]. Here we only mention metals used for CVD; other substrates will be mentioned later on in Sections 5.2, 5.3 and 5.4.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…Figure 4 shows selected C 1s and Ir 4f 7/2 core level spectra corresponding to the high Rh coverage described in Figure 3b. At low annealing temperature, the C 1s spectrum presents a narrow component at 284.06 eV (C GR , red curve), originated by the sp 2 carbon atom configurations of the unperturbed GR, 31,32 and a shoulder at 284.37 eV (C M , orange curve), a sign of metalÀGR bond formation. With increasing annealing temperature, the lower BE component increases in intensity at the expense of the higher BE peak, which disappears after annealing to T = 840 K. The Ir 4f 7/2 core level spectrum presents a similar trend: the intensity of the Ir S surface component at 60.31 eV due to first-layer Ir atoms 32,43 (black curve) increases with increasing temperature, while the small component Ir C (yellow curve), lying between the bulk Ir B (gray curve) and surface Ir S peaks, disappears after annealing to 840 K.…”
Section: Articlementioning
confidence: 99%
“…While in the atop region the Ir substrate atom lies right in the center of the carbon ring, the fcc region (hcp region) centers an Ir fcc site (hcp site) in the honeycomb lattice. 12 It is important to underline that GR/Ir(111) 31,32 represents, in analogy with what observed on Pt(111), 33 the hallmark of a low interacting and quasi-freestanding GR layer.…”
Section: Articlementioning
confidence: 99%
“…This does not seem to have been reported at the time of writing, but if such methods prove to be feasible it would open-up the possibility of transferring GNFs to a variety of substrates rather than just making them on graphene. Graphene layers have also been produced on surfaces, either by removal of layers from a SiC crystal surface (Hass et al, 2008) or by chemical vapour deposition (Obraztov, 2009) These methods might also be adaptable to the production of GNFs especially in light of recent work which showed that dome-shaped carbon nanoislands may be produced on the (111) surface of Ir (Lacovig et al, 2009). Once sheets of 2-D graphene are produced, GNFs have to be "cut" from them which has currently been done by a variety of methods; combined e-beam lithography and plasma etching (Berger et al, 2006;Schedin et al, 2007;Neubeck el al., 2010), chemical stripping , scanning tunneling microscope lithography (Tapaszto et al, 2008) and atomic force microscope lithography (Neubecket al, 2010), hydrocarbon lithography (Meyer et al, 2008) and catalytic cutting by atoms (Datta et al, 2008;Ci et al, 2008;Ci et al 2009;Campos et al, 2009).…”
Section: Top-down Production Of Gnfsmentioning
confidence: 99%